1984
DOI: 10.1051/agro:19840408
|View full text |Cite
|
Sign up to set email alerts
|

Efficacité de la coccinelle aphidiphage Semiadalia undecimnotata Schn. en serre

Abstract: RÉSUMÉLast-instar larvae of Semiadatia undecimnotata were used in inundative releases against eggplant aphids in the glasshouse. The number of larvae placed on each plant was determined according to the feeding rate of this instar and the total biomass of aphids. In most cases, these biological treatments induced a very appreciable decrease of aphid populations. In spite of these hopeful results, the method seems difficult to apply in large glasshouses. The main reasons for this are : the reproductive potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Here, the fourth instar showed better predation activity than the third larval instar and the adult consumed more aphids as compared to the 3 rd and 4 th instar grubs. Possibly because they have higher energy requirements (Ahlawat et al, 2008;Mishra et al, 2012) and store energy for future development and metamorphosis (Ferran & Larroque, 1977). Earlier studies reported that older instar required more food than the previous instar due to bigger size, longer duration and accumulated nutrients for the pupal period (Pandi et al, 2012;Işikber, 2005;Prabhakar & Roy, 2010).…”
Section: Interspecific Predation Among Different Instars Of Coccinell...mentioning
confidence: 99%
“…Here, the fourth instar showed better predation activity than the third larval instar and the adult consumed more aphids as compared to the 3 rd and 4 th instar grubs. Possibly because they have higher energy requirements (Ahlawat et al, 2008;Mishra et al, 2012) and store energy for future development and metamorphosis (Ferran & Larroque, 1977). Earlier studies reported that older instar required more food than the previous instar due to bigger size, longer duration and accumulated nutrients for the pupal period (Pandi et al, 2012;Işikber, 2005;Prabhakar & Roy, 2010).…”
Section: Interspecific Predation Among Different Instars Of Coccinell...mentioning
confidence: 99%